Preventive Competence of a Teacher-Psychologist as a Factor of his Professional Development - Shempeleva, N.I.; Pestova, I.V. (Bulletin of Practical Psychology of Education, 2021)
The article describes the system of formation of professional competencies of specialists who carry out their work in the field of prevention of social risks of minors. The components of this system and pedagogical conditions for the formation of preventive competence are also described. The need to develop competencies in the field of preventive activities is associated with the contradictions between the need for objects of preventive work and the availability of professional capabilities of specialists. These contradictions were identified in the course of specially conducted opinion polls. The existing methods and means for the formation and development of the above competencies — due to the presence of contradictions — are not sufficiently effective. In this regard, the article pays special attention to describing such a method of developing professional preventive competencies as an internship platform. It also provides a description of the application of innovative preventive practices using modern digital technologies in the framework of the internship site. В статье описывается система формирования профессиональных компетенций специа-листов, осуществляющих свою работу в сфере профилактики социальных рисков несо-вершеннолетних. Также описываются компоненты данной системы и педагогические ус-ловия формирования профилактической компетентности. Необходимость формирова-ния компетенций в сфере профилактической деятельности связана с противоречиями между потребностью объектов профилактической работы и наличием профессиональ-ных возможностей специалистов. Данные противоречия были выявлены в ходе специаль-но проведенных социологических опросов. Существующие способы и средства формиро-вания и развития вышеуказанных компетенций — ввиду наличия противоречий — не яв-ляются эффективными в достаточной мере. В связи с этим в статье уделяется особое внимание описанию такого способа развития профессиональных профилактических ком-петенций, как стажировочная площадка. Также приводится описание применения иннова-ционных профилактических практик с использованием современных цифровых техноло-гий в рамках деятельности стажировочной площадки.